Reduced Effect of Percutaneous Renal Denervation on Blood Pressure in Patients With Isolated Systolic Hypertension. Issue 1 (January 2015) - Ewen, Sebastian; Ukena, Christian; Linz, Dominik; Kindermann, Ingrid; Cremers, Bodo; Laufs, Ulrich; Wagenpfeil, Stefan; Schmieder, Roland E.; Böhm, Michael; Mahfoud, Felix
<x xml:space="preserve">Abstract</x> Renal denervation can reduce blood pressure in certain patients with resistant hypertension. The effect in patients with isolated systolic hypertension (ISH, ≥140/<90 mm Hg) is unknown. This study investigated the effects of renal denervation in 126 patients divided into 63 patients with ISH and 63 patients with combined hypertension (CH, ≥140/≥90 mm Hg) defined as baseline office systolic blood pressure (SBP) ≥140 mm Hg despite treatment with ≥3 antihypertensive agents. Renal denervation significantly reduced office SBP and diastolic blood pressure (DBP) at 3, 6, and 12 months by 17/18/17 and 5/4/4 mm Hg in ISH and by 28/27/30 and 13/16/18 mm Hg in CH, respectively. The reduction in SBP and DBP in ISH was lower compared with patients with CH at all observed time points (P<0.05 for SBP/DBP intergroup comparison). The nonresponder rate (change in office SBP <10 mm Hg) after 6 months was 37% in ISH and 21% in CH (P<0.001). Mean 24-hour ambulatory SBP and DBP after 3, 6, and 12 months were significantly reduced by 10/13/15 and 6/6/9 mm Hg in CH, respectively. In patients with ISH the reduction in systolic ambulatory blood pressure was 4/8/7 mm Hg (P=0.032/P<0.001/P=0.009) and 3/4/2 mm Hg (P=0.08/P<0.001/P=0.130) in diastolic ambulatory blood pressure after 3, 6, and 12 months, respectively. The ambulatory blood pressure reduction was significantly lower after 3 and 12 months in SBP and after 12 months in ambulatory DBP, respectively. In conclusion, renal denervation reduces office and ambulatory blood pressure in patients with ISH. However, this reduction is less pronounced compared with patients with CH.